Elasticity of the Property Tax in the Czech Republic - Očkajová, Paulína; Dušek, Libor; Miklánek, Tomáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
The main motivation of this thesis is to investigate whether, as already claimed by early economists such as Ricardo, the property tax is indeed the ideal tax because of perfectly inelastic tax base. For this purpose, I estimate the revenue elasticity of the property tax with respect to tax rates in the Czech Republic using municipality-level data on property tax revenue, tax rates and municipality characteristics during the period of 2004 to 2017. The research design exploits a variation in tax rates across municipalities and years caused by a policy change in 2008 when municipalities obtained an option to multiply the final tax liability of taxpayers by a so-called local coefficient. Using difference-in-differences estimator, I find the total revenue elasticity to be 0.76, while theoretically it should be one under perfectly inelastic tax base. However, further analysis indicates that the less-than-one elasticity is primarily due to substantial exemptions rather than behavioural responses in the tax base.
Vedoucí práce: Libor Dušek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses